Language barriers and postoperative opioid prescription use after total knee arthroplasty - Kevin H. Nguyen; Aksharananda Rambachan; Derek T. Ward; Solmaz P. Manuel (Elsevier, 2022)
Background: Patients with limited English proficiency (LEP) face difficulties in access to postoperative follow-up care, including post-discharge medication refills. However, prior studies have not examined how utilization of prescription pain medications after discharge from joint replacement surgeries differs between English proficient (EP) and LEP patients. Objective: This study explored the relationship between English language proficiency and opioid prescription refill requests after hospital discharge for total knee arthroplasty (TKA). Methods: This was an observational cohort study of patients ≥18 years of age who underwent TKA between January 2015 and December 2019 at a single academic center. LEP status was defined as not having English as the primary language and requesting an interpreter. Primary outcome variables included opioid pain medication refill requests between 0 and 90 days from discharge. Multivariable logistic regression modeling calculated the odds ratios of requesting an opioid refill. Results: A total of 2148 patients underwent TKA, and 9.8% had LEP. Postoperative pain levels and rates of prior opioid use did not differ between LEP and EP patients. LEP patients were less likely to request an opioid prescription refill within 30 days (35.3% vs 52.4%, p < 0.001), 60 days (48.7% vs 61.0%, p = 0.004), and 90 days (54.0% vs 62.9%, p = 0.041) after discharge. In multivariable analysis, LEP patients had an odds ratio of 0.61 of requesting an opioid refill (95% CI, 0.41-0.92, p = 0.019) within 30 days of discharge. Having Medicare insurance and longer lengths of hospitalization were correlated with lower odds of 0-30 days opioid refills, while prior opioid use and being discharged home were associated with higher odds of opioid refill requests 0-30 days after discharge for TKA. Conclusions: Language barriers may contribute to poorer access to postoperative care, including prescription medication refills. Barriers to postoperative care may exist at multiple levels for LEP patients undergoing surgical procedures.